Rainbow Connection Number on Amalgamation of General Prism Graph - Rizki Hafri Yandera; Yanne Irene; Wisnu Aribowo (InPrime: Indonesian Journal of Pure and Applied Mathematics, 2019)
AbstractLet  be a nontrivial connected graph, the rainbow-k-coloring of graph G is the mapping of c: E(G)-> {1,2,3,…,k} such that any two vertices from the graph can be connected by a rainbow path (the path with all edges of different colors). The least natural number